25th Annual Meeting of the German Society for Travel Medicine (DFR) Berlin, Germany, 15–17 September 2022 - Küpper, Thomas (Health Promotion & Physical Activity, 2022)
This year the Annual Meeting in Berlin (September 15th to 17th) was the 25th one of the German Society of Travel Medicine and therefore it included some celebration. The scientific part included a wide variety of topics. Beside of ‘typical’ ones like malaria prevention and new vaccines there were lectures about space tourism (Prof. R. Gerzer), environmental risks (earthquakes – Dr. J. Lauterjung, altitude medicine – Dr. S. Baniya, and poisonous snakes – Dr. C. Pechmann). Prof. M. Tannheimer discussed quick ascents to extreme altitude by pre-acclimatized climbers while Dr. Kattner reported news about tick borne diseases. Yellow fever (Dr. K. Kling) and Hepatitis B in Nepal (Dr. A.S. Menner) were discussed intensively. Another topic was different aspects of cruise shipping (Prof. T.W. Heggie, C. Kopp, L. Damm). Prof. T. Küpper touched a ‘hot iron’: Ethical considerations in travel medicine. There was a special invitation to young scientists, students and clinicians with a specific event. Poster presentations added topics for discussions. The presented abstracts include lectures and posters and are listed in alphabetical order of the first author.